2017
DOI: 10.1016/j.socscimed.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated support from children and later-life health in the United States and China

Abstract: Past research has shown that anticipated support, the belief that someone will provide support if needed, benefits health. Few studies considered whether the relationship between anticipated support and health depends on the source of such support. This project addresses this gap and examines how anticipated support from children is related to older parents' health and whether such support can be replaced by anticipated support from other relatives and friends. Ordered logit and negative binomial regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 49 publications
(72 reference statements)
6
18
0
Order By: Relevance
“…Our study suggests that the quality of parent–child relationships may matter most, not the quantity of children. For example, a recent study found that anticipated support from children, the belief that children would provide support if needed, was associated with older parents’ better self-rated health 21. This may have important implications for China since the one-child policy has led to smaller family size and changes in family structure and relations.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that the quality of parent–child relationships may matter most, not the quantity of children. For example, a recent study found that anticipated support from children, the belief that children would provide support if needed, was associated with older parents’ better self-rated health 21. This may have important implications for China since the one-child policy has led to smaller family size and changes in family structure and relations.…”
Section: Discussionmentioning
confidence: 99%
“…Our results on females and rural residents being more vulnerable to depression than their counter parts are in line with other studies on China such as C. Cheng (2017) and B. Hu and Wang (2019).…”
Section: Resultssupporting
confidence: 92%
“…This is similar to Zhang et al (2016) where overweight subjects are not depressed unlike the underweight group when compared to those of normal weight. The effect of chronic disease, ADL, self-reported health and social activities also have the expected impacts and align with other studies on the Chinese elderly (C. Cheng, 2017;Q. Wang & Tian, 2018;.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations